Evaluation of Preparedness Senior High School 1 Sikur in Responding The Changes of Islamic Character Due to Development of Halal Tourism in East Lombok Regency - Amelia, Hutri Rizki (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
The purpose of the research is to evaluating the preparedness of Senior High School 1 Sikur in responding the changes of Islamic character affected by development of halal tourism at Lombok Timur regency, Nusa Tenggara Barat province, Indonesia. This research used Qualitative, Observation collecting data technic, interview and documentation. Data analysis in this research was used data reduction technic, data interpretation and taking of conclusion. The result of this research is the preparedness of Senior High School 1 Si Sikur in responding the changes of Islamic character affected by development of halal tourism seems good enough. Either of school programs for spiritual character building through Imtaq, Tilawah and religion lectured that has been told by Tuan Guru Haji (TGH), and Dhuhur Pray congregation everyday. The late students will be punished by stand in the field around 30 minutes. The characteristic of environmental care showed with mutual activity is held once a month, and planting trees in cooperation with the Department of agriculture. Keywords : Development of Islamic Character, Halal Tourism